Princess Bari - Sook-yong, Hwang (Periscope, 2015)
A modern-day quest novel from one of Korea's most renowned novelists. Princess Bari tells the story of a young girl, frail and brave, who escapes from famine and death in North Korea in the 1990s. Seeking refuge in China before crossing oceans in the hold of a cargo ship, she disembarks in London, with its strange mix of different cultures, religions, and languages. In this foreign city, Bari becomes a masseuse, but she doesn't just heal the body, she also comforts souls, having learnt from her beloved grandmother to read the pain and nightmares of others. Alone and in a strange land, Bari will have to fight, through pain and deepening sadness, to find love and the will to stay alive. With Princess Bari, Hwang Sok-Yong entwines an old Korean myth -- of an abandoned princess travelling to the ends of the earth to find the elixir of life, which will bring peace to the souls of the dead -- with the ethereal and haunting backdrop of the modern world.